Sosialisasi Pentingnya Penerapan 3M di Era New Normal Desa Riding Panjang - dita hardiani; Hazbi an Yasypiaka; Muhammad Nur Hidayat; Siti Nursiah; Bayu Pratama (Jurnal Pengabdian Masyarakat Indonesia, 2021)
The Covid-19 pandemic has had an impact on all levels of society, including the people of Bangka. Positive cases of Covid-19 in Riding Panjang Village are still relatively high and continue to grow. This results in a high transmission rate. Therefore, this problem needs to be considered so that it is handled as soon as possible to help prevent the spread of Covid-19. Public awareness of the importance of adhering to health protocols is still very minimal, this is what has become the main cause of transmission of the Covid-19 virus. Based on these problems, there is a need for public awareness to change behavior patterns to better comply with health protocols in tackling the spread of Covid-19. With that, it is important to make an effort that can make the public's mindset aware of the importance of complying with health protocols, namely by holding outreach activities in order to prevent the spread of Covid-19. This socialization was conducted in Bukit Tulang Hamlet, Riding Panjang Village, Belinyu District, Bangka Regency, Bangka Belitung Islands Province. As for the activities achieved from this socialization, the community is more concerned with complying with health protocols such as wearing masks, maintaining distance, and washing hands.